대퇴 과 관절 연골 결손의 자가 연골 세포 이식술 - 송철(Chol Song); 김정만(Jung-Man Kim); 성병윤(Byeong-Yoon Sung); 공윤배(Yoon-Bae Kong); 라기항(Ki-Hang Ra) (The journal of the Korean Orthopaedic Association, 2009)
목 적: 대퇴 과 관절 연골 결손을 위한 자가 연골 세포 이식술 후 임상적 및 조직학적 중기 추시 결과를 보고하고자 한다. 대상 및 방법: 자기 공명 영상 및 관절경 소견상 슬관절 대퇴 과 연골 결손을 보인 Outerbridge 분류 제 4 등급 24명 24관절에 자가 연골 세포 이식술을 시행하였다. 평균 연령은 42.8세였고 추시 기간은 평균 53.2개월(20-82개월)이었다. 임상적 경과는 수술 전과 최종 추시 시의 HSS 점수와 Lysholm 점수로 평가하였고, 자기 공명 영상의 SPGR기법으로 관절 연골 재생 상태를 확인하였다. 관절경 추적 및 생검은 8예에서 시행하였다. 결 과: 자기 공명 영상 소견상 1예를 제외한 23예에서 관절 연골은 성공적으로 재생되었으며, HSS 점수는 수술 후 최종 추시 시 모두 향상된 결과를 보였고(p＜0.0001), Lysholm 점수는 모든 군에서 향상된 결과를 보였으나 외상성 관절 연골 골절에서만 통계적으로 유의하지 않았다(p=0.1257). 조직 생검 결과 8예 모두에서 초자 연골양 조직으로 재생되었다. 결 론: 자가 연골 세포 이식술은 대퇴 과 연골 결손 치료시 우수한 결과를 보였고 골관절염 시에는 근위 경골 절골술을 같이 시행함으로서 비교적 좋은 결과를 보였다. 그러나 확실한 결론을 얻기 위해서는 장기적인 추시가 요구된다. Purpose: To evaluate the midterm clinical and histological results after autologous chondrocyte implantation (ACI) for an articular cartilage defect of the distal femoral condyle. Materials and Methods: Twenty four cases with an articular cartilage defect (Outerbridge grade IV) of the femoral condyle that was confirmed by MRI and the arthroscopic findings underwent ACI. Their mean age at the time of surgery was 42.8 years and the mean follow-up period was 53.2 months (range, 20-82 months). At the last follow up, the articular cartilage view (SPGR) of MRI was examined and the clinical results were evaluated using the HSS and Lysholm scores. In 8 cases, second-look arthroscopy and biopsy were performed and evaluated using histological and histochemical methods. Results: All cases except for one showed well-regenerated articular cartilage on MRI. All cases showed significant clinical improvement in the HSS and Lysholm scores (p＜0.0001), with the exception of the Lysholm score of an articular cartilage fracture. Histologically, the regenerated tissue appeared to be a hyaline-like cartilage in all specimens. Conclusion: ACI for the treatment of articular cartilage defects of the distal femoral condyle showed a good clinical and MRI results. In OA, the clinical results were relatively acceptable after an associated high tibial valgus osteotomy. However, a longer term follow-up study will be needed to reach a final conclusion. KCI Citation Count: 2